INDONESIAN DIASPORA EMPOWERMENT: A CONCEPT IN STRENGTHENING DIPLOMACY FOR NATIONAL DEFENSE - Lily Andayani (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2020)
The existence of the Indonesian Diaspora abroad cannot be separated from the development of the global environment. The global constellation dynamically moves ahead with the complexity of inter-correlation and inter-implication multi-dimensional of the state, with non-military, military, and hybrid potential threats. The rapid progress of transportation and information technology, and cyber technology well as has become escalating turbulence over global dynamics. This context is an urgency for Indonesia to utilize Indonesian Diaspora for national interests and national defense. This paper aims to analyze the empowerment of Indonesian Diaspora in strengthening diplomacy for national defense. The author uses a qualitative approach by raising the theory of empowerment and diplomacy elaborated with the rights and obligations of defending the country upon the Indonesian Diaspora. Various data and information from literature and other open sources are used in this paper. Some of the emerging phenomena related to the Indonesian Diaspora are contested with the development of public diplomacy practices correlated with challenges and threats in the approach of national security and defense. The conclusion portrays the importance of continuing the empowerment of the Indonesian Diaspora in strengthening efforts to fight for and protect national interests, including national defense.